Expression of the KAL gene in multiple neuronal sites during chicken development. - Legouis, R (1993)
The human KAL gene is responsible for the X chromosome-linked Kallmann syndrome. A partial cDNA sequence from the chicken KAL homologue was determined and used to study expression of the KAL gene, by in situ hybridization, during chicken development, from day 6 of incubation. The KAL gene is mainly expressed in neurons of the central nervous system during the second half of embryonic life. High levels of transcript were detected in mitral neurons of the olfactory bulbs, in striatal neurons, in Purkinje cells of the cerebellum, in retinal neurons, and in isolated neurons of the brainstem and spinal cord. No expression was observed in glial cells. A low level of expression was observed in some mesenchymal derivatives. In the adult, expression is maintained or increased in several neuronal populations, especially in optic tectum and striatum. A possible role for the KAL protein in synaptogenesis at these stages is discussed. These results in the chicken embryo help to elucidate the mechanisms of anosmia and gonadotropin-releasing hormone deficiency, which define Kallmann syndrome. In addition, most of the occasional symptoms described in Kallmann syndrome patients, such as cerebellar ataxia, abnormal ocular movements, abnormal spatial visual attention, mirror movements, and renal aplasia, could be ascribed to malfunction of areas that, in the chicken, express the KAL gene.